The demand for soft skills and impacts of training and development on human resource outcomes and firm performance for the Malaysian manufacturing industry - Lok, Bee Lan (2022)
The Malaysian manufacturing industry, which is the country’s second-largest contributor to GDP, has experienced dramatic changes in the skills required where the demand for soft skills is becoming much more important than ever before. However, there is limited knowledge of the current and future demand for specific areas of soft skills. Although training and development (T&D) is increasingly seen as vital in addressing and bridging the soft skills demand and gap, there is a lack of empirical evidence on the impact of soft skills T&D on human resource and firm performance. In response, this research aims to: (i) identify the soft skills demanded by employers; and (ii) develop a research model based on human capital theory and resource-based view to empirically investigate the impact of soft skills T&D on human resource outcomes (HRO) and firm performance (FP). Using a random sampling method, a questionnaire survey was conducted in Selangor, Johor, Penang, and Perak in Malaysia, these are the four states where most of the manufacturing firms are located. The results showed that the current top three soft skills in demand are “teamwork”, “emotional intelligence” (EQ), and “moral and professional ethics”. The top skills for future demand are “EQ”, “teamwork” and “thinking skills”. The English language is in high demand now and in the future. The most significant skill gap is found in EQ, followed by thinking skills and entrepreneurship. The findings of hypothesis testing using the PLS-SEM technique supported the hypothesised relationships between (i) T&D and HRO and (ii) HRO and FP, but not the relationship between T&D and FP. In addition, HRO is found to fully mediate the relationship between T&D and FP. These findings provide insights into the soft skills required by the manufacturing industry, allowing stakeholders, industrial practitioners, and policymakers to make better planning on human resource management and training development. It also has practical implications for enriching resource-based view and human capital theory.